Resiliensi Psikososial Mahasiswa dengan Latar Belakang Keluarga Broken Home (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to understand the process of psychosocial resilience formation in students with broken home backgrounds. This phenomenon is important given the increasing divorce rate in Indonesia, which has an impact on the emotional well-being of the younger generation. This study uses a descriptive qualitative approach with semi-structured interviews with three students from broken homes. Data were analyzed using thematic analysis to identify emerging patterns of adaptation. The results of the study show that students' psychosocial resilience is formed through a combination of internal and external factors. Internal factors include emotional regulation skills, optimism, and self-efficacy, while external factors include social support and spirituality. Students demonstrated the ability to transform negative experiences into motivation for growth. These findings support Reivich & Shatté's theory and Social Support Theory, which emphasize the role of social support in reducing psychological stress.